A roller coaster ride: An empirical investigation of the main drivers of wheat price - Bernardina Algieri (University of Bonn, Center for Development Research (ZEF), 2013)
Over the last decade, commodity prices have registered substantial booms and busts marked by extreme volatility. Wheat in particular, one of the main non-oil commodities, has registered a roller-coaster in price levels which seems to be inconsistent with supply and demand fundamentals. To acutely investigate the drivers of wheat prices and quantify their impact, a Vector Error Correction Model (VECM) has been used. The exogenous variables have been distinguished into four groups: market-specific factors, broad macroeconomic determinants, speculative components, and weather variables. The quadriangulation of the determinants will enable us to better understand the movements in wheat price and identify the specific role of each component. The results show a mix of short and long term factors that are contributing to wheat price movements, and their effect should be taken into account in designing proper policy intervention to mitigate the negative impact of price shocks.
Keywords: C22; E31; Q11; 330; wheat price; fundamentals; speculation